Sencha Touch 2 : up and running - Kosmaczewski, Adrian (O'Reilly Media, 2013)
Launch into Sencha Touch 2 with this hands-on book, and quickly learn how to develop robust mobile web apps that look and behave like native applications. Using numerous code samples, author Adrian Kosmaczewski guides you every step of the way through this touchscreen-enabled JavaScript framework--from creating your first basic app to debugging, testing, and deploying a finished product. Learn how to craft user interfaces, build forms, and manage data, then deploy as either an HTML5 offline app or as a native app for Android, iOS, or Blackberry. Define classes and create instances with Sencha Touch's object-oriented abstraction Build user interfaces with the framework's extensive set of high-level components Develop apps that consume complex data, whether it's stored locally or on remote servers Organize your application code in a consistent, predictable, and maintainable way Use Sass stylesheets to craft a personalized look and feel for your app Debug, test, and document your app with WebKit Web Inspector, Jasmine, Siesta, and JSDuck Use the Sencha Architect UI designer and IDE to simplify complex project development.